Biannual Administrations of Azithromycin and the Gastrointestinal Microbiome of Malawian Children: A Nested Cohort Study Within a Randomized Controlled Trial - David Chaima; David Chaima; Harry Pickering; John D. Hart; Sarah E. Burr; Sarah E. Burr; Joanna Houghton; Kenneth Maleta; Khumbo Kalua; Khumbo Kalua; Robin L. Bailey; Martin J. Holland (Frontiers Media S.A., 2022)
Community-level mass treatment with azithromycin has been associated with a mortality benefit in children. However, antibiotic exposures result in disruption of the gut microbiota and repeated exposures may reduce recovery of the gut flora. We conducted a nested cohort study within the framework of a randomized controlled trial to examine associations between mass drug administration (MDA) with azithromycin and the gut microbiota of rural Malawian children aged between 1 and 59 months. Fecal samples were collected from the children at baseline and 6 months after two or four biannual rounds of azithromycin treatment. DNA was extracted from fecal samples and V4-16S rRNA sequencing used to characterize the gut microbiota. Firmicutes, Bacteroidetes, Proteobacteria and Actinobacteria were the dominant phyla while Faecalibacterium and Bifidobacterium were the most prevalent genera. There were no associations between azithromycin treatment and changes in alpha diversity, however, four biannual rounds of treatment were associated with increased abundance of Prevotella. The lack of significant changes in gut microbiota after four biannual treatments supports the use of mass azithromycin treatment to reduce mortality in children living in low- and middle-income settings.